2017
DOI: 10.1242/jcs.193086
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila WASH is required for integrin-mediated cell adhesion, cell motility and lysosomal neutralization

Abstract: The Wiskott-Aldrich syndrome protein and SCAR homolog (WASH; also known as Washout in flies) is a conserved actin-nucleationpromoting factor controlling Arp2/3 complex activity in endosomal sorting and recycling. Previous studies have identified WASH as an essential regulator in Drosophila development. Here, we show that homozygous wash mutant flies are viable and fertile. We demonstrate that Drosophila WASH has conserved functions in integrin receptor recycling and lysosome neutralization. WASH generates acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 63 publications
(96 reference statements)
5
40
1
Order By: Relevance
“…Interestingly, a mutation in VPS35 (D620N) (Vilariño-Güell et al, 2011;Zimprich et al, 2011) that is associated with earlyonset Parkinson's disease has been shown to diminish the interaction of the SHRC with VPS35 and impair vesicular trafficking from the late endosome (Follett et al, 2013;McGough et al, 2014;Zavodszky et al, 2014). Studies in Drosophila have recently shown important roles for WASH in regulating integrin receptor trafficking and lysosome acidification (Nagel et al, 2017). A similar role for WASH in the recycling of integrins has been seen in mammalian cells .…”
Section: Jmymentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, a mutation in VPS35 (D620N) (Vilariño-Güell et al, 2011;Zimprich et al, 2011) that is associated with earlyonset Parkinson's disease has been shown to diminish the interaction of the SHRC with VPS35 and impair vesicular trafficking from the late endosome (Follett et al, 2013;McGough et al, 2014;Zavodszky et al, 2014). Studies in Drosophila have recently shown important roles for WASH in regulating integrin receptor trafficking and lysosome acidification (Nagel et al, 2017). A similar role for WASH in the recycling of integrins has been seen in mammalian cells .…”
Section: Jmymentioning
confidence: 93%
“…This is mediated by a TRIM27-containing ubiquitin ligase complex that also contains MAGEL2 and UBE2O, and is regulated by the deubiquitinase USP7 (Hao et al, 2015). Finally, although deletion of WASH in Drosophila was initially found to impair oogenesis and larval development (Linardopoulou et al, 2007;Liu et al, 2009), a recent study using a different WASH mutant showed that homozygous wash mutant flies are viable and fertile (Nagel et al, 2017). This discrepancy was likely caused by a secondsite lethal mutation in the Drosophila strain used in the former studies.…”
Section: Jmymentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the WASH complex halts the maturation and trafficking of lysosomes in Dictyostelium (Carnell et al, 2011; Park et al, 2013) and phagolysosomes in Drosophila macrophages (Nagel et al, 2017). In Dictyostelium , instead of undergoing their normal transition into neutral post-lysosomes from wash -knockout (KO) cells remain acidic and fail to undergo exocytosis (Carnell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As the V-ATPase has F-actin-binding domains (Holliday et al, 2000; Huss et al, 2011), there could be direct coupling between WASH-generated F-actin and the V-ATPase that coordinates its trafficking. Recent work has also found that WASH and V-ATPase can be co-immunoprecipitated from Drosophila cells, suggesting a possible direct interaction between the complexes (Nagel et al, 2017). …”
Section: Introductionmentioning
confidence: 99%